A review of single-handed coaxial phacoemulsification technique for cataract surgery - Setyandriana, Yunani; Zain, Nurul Attikah (Diponegoro International Medical Journal, 2024)
Background: Currently, cataract surgery is categorized into two main techniques: phacoemulsification and femtosecond-laser-assisted-cataract-surgery (FLACS)..Objective: The objective of this study was to present a comprehensive review of the existing literature on the single-handed coaxial phacoemulsification technique used in cataract surgery.Methods: The study conducted a systematic review of PubMed, EMBASE, and Scopus databases. The participants included in our study were individuals diagnosed with simple cataract. These individuals had treatment using either single-handed or two-handed phacoemulsification or FLACS techniques. Publications predating the year 2000 were omitted from consideration. The abstracts of the publications were analyzed utilizing the PRISMA diagram, and those deemed to be somewhat and highly pertinent were incorporated. In total, a comprehensive analysis was conducted on six research, consisting of two randomized controlled trials (RCTs) and four non-randomized controlled trials (nonRCTs).Results: The visual acuity (VA) shown a statistically significant improvement in the single-handed group compared to the two-handed group at the one-week postoperative assessment (p<0.05). However, this difference was not observed at the one-month and three-month postoperative assessments.  The single-handed group had a smaller angle of error (AE) compared to the two-handed group (p=0.005). Additionally, another study observed an improvement in visual acuity (VA) in individuals who underwent single-handed, two-handed group, and femtosecond laser-assisted cataract surgery (FLACS). However, the study did not identify any statistically significant variations in VA improvement across the three groups. There was no statistically significant difference observed among the three groups in relation to ECL and CCT. The intraoperative phacoparameter exhibited a statistically significant decrease in the single-handed group (P<0.01) compared to the two-handed group, while it did not differ substantially from the femtosecond laser-assisted cataract surgery (FLACS) group.Conclusion: When comparing the two-handed phacoemulsification technique to FLACS, it was observed that a single-handed method exhibited a reduced angle of error, minimized corneal damage, and exhibited early visual outcomes.